The taxonomic status of Phrynopus pereger Lynch 1975 (Amphibia, Anura, Leptodactylidae) - Lehr, Edgar; Guilar, César (Zootaxa, 2006)
Live and freshly preserved specimens of Phrynopus pereger have terminal discs with a small, papilla-like projection and weak, interrupted circumferential grooves separating the disc from a pad. Based on external morphological and osteological characters Phrynopus pereger is transferred to Eleutherodactylus. Information on its natural history and distribution, and photos in life are provided. All Peruvian Phrynopus (except P. pereger) occur at elevations between 2600 and 4400 m.